AC/Ni(OH)2 as a porous electrode material for supercapacitors with high-performance. (10th December 2022) - Qin, Zhao; Liu, Jie; Sun, Biemin; Zou, Hanjun; Chen, Lingyun; Xu, Yanqin; Cao, Yuan; Chen, Changguo
Highlights: A novel porous AC/Ni(OH)2 composite was prepared by two-step hydrothermal method and used for the first time as electrode material. The specific capacity of the AC/Ni(OH)2 was 183.7 mAh g −1 at 1 A g −1, and the capacity retention rate was 90.2% after 3000 cycles. The AC/Ni(OH)2 // AC hybrid supercapacitor showed high energy density of 37.58 Wh kg −1 and power density of 6400 W kg −1 . Abstract: Commonly used nickel-based compounds as electrode materials have low rate capability and poor long-term cycling stability, which limit their practical applications. In this case, it may be an idea to synthesize a composite combining carbon-based electric double layer capacitors and pseudocapacitors. In this study, a novel porous AC/Ni(OH)2 composite was prepared by hydrothermal method, which was used as an electrode for a supercapacitor for the first time with a specific capacity of 183.7 mAh g −1 at 1 A g −1 and a cycling stability of 90.2% after 3000 cycles. Moreover, there is a hybrid supercapacitor (HSC) device assembled by using AC/Ni(OH)2 and active carbon (AC). On the condition of having a power density of 801.5 W kg −1 with the voltage window of 1.6 V, the HSC produces a high energy density of 37.58 Wh kg −1, maintaining an outstanding capacitance retention of 88.5% after 3000 cycles at current density of 8 A g −1 . Therefore, AC/Ni(OH)2 electrode material helps to improve the performance of the HSC device and can be used as an electrode material for the development of energy storage devices in the future. Graphical abstract: A novel porous AC/Ni(OH)2 composite was synthesized by a two-step hydrothermal method, using AC/Ni(OH)2 as the positive electrode and AC as the negative electrode to assemble a hybrid supercapacitor with good energy storage performance. Image, graphical abstract